A New Proposed Pendulum-Like with Attraction-Repulsion mechanism Algorithm for Solving Optimization Problems - Abed I.A.; Koh S.P.; Sahari K.S.M.; Tiong S.K.; Ali M.M.; Abdul Kadhim A.A. (Institute of Physics Publishing, 2023)
This work aims to contribute to the domain of new modification in electromagnetism-like (EM) algorithm, which will be referred to in this work as pendulum-like with attraction-repulsion mechanism algorithm (PA). PA algorithm has been constructed with the purpose of solving inverse kinematics (IK) problem. The proposed new algorithm mimics the concepts of a simple physical pendulum and is derived as a local search in order to promote the performance of the EM algorithm. Comparisons between the suggested PA with the available algorithms, such as genetic algorithm (GA) and EM were conducted using two mathematical test functions. On top of the testing, the PA algorithm is tested to solve the problem of IK for a four degree-of-freedom (DOF) planar robot. The simulation results indicate that the PA algorithm outperforms other approaches in terms of accuracy and the speed of convergence through the errors and the decreasing of objective with iterations as mention in presented tables and figures, on top of being able to successfully solve the IK problem with multiple robot configurations. 2020 Published under licence by IOP Publishing Ltd.